2002
DOI: 10.1016/s0960-9822(02)01319-2
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish as a Model Organism for the Identification and Characterization of Drugs and Genes Affecting p53 Signaling

Abstract: p53 and its main negative regulator, Mdm2, are key players in mammalian cancer development. Activation of the transcription factor p53 through DNA damage or other stresses can result in cell cycle arrest, apoptosis, or both. Because of the absence of characterized p53 signaling in zebrafish (Danio rerio), we have studied the roles of Mdm2 and p53 in zebrafish by generating early embryonic knockdowns and examined the involvement of p53 in DNA damage-induced apoptosis. p53-deficient embryos, induced by injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
307
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(329 citation statements)
references
References 21 publications
(1 reference statement)
19
307
0
3
Order By: Relevance
“…(The p53 M214K mutation is in the DNA binding domain.) We used gamma-radiation to activate p53, as radiation is an insult that is known to activate the p53 pathway[33]. We have previously shown that the p53 mutant no longer up-regulates p21 in response to irradiation[22].…”
Section: Resultsmentioning
confidence: 99%
“…(The p53 M214K mutation is in the DNA binding domain.) We used gamma-radiation to activate p53, as radiation is an insult that is known to activate the p53 pathway[33]. We have previously shown that the p53 mutant no longer up-regulates p21 in response to irradiation[22].…”
Section: Resultsmentioning
confidence: 99%
“…RhoA knockdown induces apoptosis during zebrafish embryogenesis It is reported that the opaque regions in the developing zebrafish embryos implicate cell death and could be a consequence of apoptosis (Langheinrich et al, 2002). To examine this, we analysed the phenotypic embryos by TUNEL assay.…”
Section: Resultsmentioning
confidence: 99%
“…In zebrafish, CPT induces p53 activation and causes apoptosis (Langheinrich et al, 2002;Le et al, 2009). Therefore, we tested whether MLL5-mediated p53 activation by CPT was conserved in developing zebrafish.…”
Section: Cpt-induced Downregulation Of Mll5 Is Conserved In Developinmentioning
confidence: 99%